Growth and yield response of groundnut [Arachis hypogaea (Linn.)] under Meloidogyne incognita infection to furfural synthesised from agro-cellulosic materials - Adenike, Fabiyi Oluwatoyin (Journal of Tropical Agriculture, 2021)
Groundnut is widely cultivated for its edible oil. A constraint to production is infestation by plant parasitic nematodes. Synthetic nematicides are employed in suppression of soil nematodes, with effective outcome. However, risk of emergence of resistant nematode strains and health hazards are associated with constant use of nematicides. Hence, there is a need for identifying safer alternatives to synthetic nematicides. Huge quantities of lignocellulosic wastes are generated from harvesting and processing of agricultural products in Nigeria. Colossal amount of resources is wasted through burning and decomposition, which at the same time translates to environmental pollution and public nuisance. These wastes can be utilized positively in the production of furfural. Efficacy of furfural from agricultural biomass waste was investigated as a possible alternative to conventional synthetic nematicides. Agricultural biomass wastes were collected and refluxed with sulphuric acid to produce furfural. Growth response of groundnut plants increased significantly with the highest dose (50 mL) of furfural. Reduction in nematode population in soil and roots of treated plants was observed, with corresponding increase in yield at harvest. Furfural from sorghum husk and corn cob reduced nematode population significantly. Results indicated that furfural could be practically applied in the management of nematode pests of groundnut.